STUDI KINETIKA FLOTASI BATUBARA DI DALAM SEL FLOTASI KOLOM (COLUMN FLOTATION CELL) - Harminuke Eko Handayani, Rr.
Abstract: Since the column flotation cell was discovered, it has attracted much attention for its in separation of valuable mineral, especially fine coal particles which represent good result compared to convention flotation cell. This experiment will perceive how column flotation cell can separate clean coal from its mineral matter with considering the kinetics. To know quantitatively the floating of particles in a dimension of fraction, therefore we should know the constant of its flotation rate using the equation of kinetics flotation. This statement can be formulated in recovery form as general equation, that is {dR} = k1(1-R), so from the above general equation, the multi components experiment data in plot using the equation 1n (1 - R - Rx) = 1n (1 - Rx) - k1t , and for the experiment of double component, there is a component which floating in rate and also a component which floating slowly. The equation is 1n(1-Rs) = - kst and 1n (1 -Rf) = - kft, so it is known the constant of flotation rate for each dimension of fraction. From this experiment it would be found out the influence of weight composition of dimension fraction to its constant of flotation rate. The result of the experiments represent that coal with separated multi components experiment has the higher rate compared to simultaneous flotation. For double component experiment, the fraction size -100+200 mesh is the faster float component compared to -65+100 mesh fraction if the increases of flotation rate constant occurred at the same time with the decreases of fraction size composition of -65+100 mesh in feed.